The Anti-Microbial Properties of Triticum aestivum (Wheat Grass) Extract - Sundaresan, Athul; Selvi, Arul; Manonmani, H.K. (International Journal of Biotechnology for Wellness Industries, 2015)
Wheat grass, one of the members of Poaceae family, has been considered for very efficient therapeutic drugs. Current study was aimed at evaluation of antimicrobial properties of wheat grass extracts. The 7th., 14th., and 21st. day wheat grass extracts of five different solvents (water, ethanol, methanol, ethyl acetate and hexane) were assayed for antimicrobial activity using turbidity tests. All these extracts showed antibacterial activity against seven food borne pathogens. Amongst them hexane extracts from 7th day old wheat grass showed maximum antibacterial activity especially more against Yersinia enterocolitica and Listeria monocytogenes. The HPLC purified extract was observed to create pores on the cell wall of the bacterial cells as observed under Scanning Electron Microscope and also influenced flattening and shrinkage of bacterial cells indicating probable effect on the membrane of the pathogenic bacteria.